ALUR PROSES PRODUKSI SAYUR ORGANIK PADA CV. REJA MAYUR - Rahayu, Niken Calista (Fakultas Pertanian, Program Studi Agroteknologi, 2023)
Vegetables are food ingredients that are needed by humans, but there are other things that must be known that most vegetables consumed today cannot be separated from the influence of chemical substances. Vegetables cultivated under the influence of chemicals will mostly contain chemical residues which can be bad for humans who consume them continuously. Therefore, it is necessary to have an agricultural system that is more environmentally friendly or commonly referred to as organic farming to deal with this problem. The purpose of this study is to describe the process flow of organic vegetable production at CV. Reja Mayur. This research is expected to provide information to the public regarding the flow of organic vegetable production and can become a database for further research. The research method used is the method of active participation and interviews, where the results will be analyzed using descriptive methods. The results of this study are on CV. Reja Mayur has 7 stages of organic vegetable production which consist of tillage, seeding, transfer of seeds, nutrition, maintenance, pest control, and harvest and post-harvest.